Drivers of antimicrobial resistance in layer poultry farming: Evidence from high prevalence of multidrug-resistant Escherichia coli and enterococci in Zambia - Steward Mudenda; Flavien Nsoni Bumbangi; Kaunda Yamba; Musso Munyeme; Sydney Malama; Moses Mukosha; Mwendalubi Albert Hadunka; Victor Daka; Scott Kaba Matafwali; Godfrey Siluchali; Geoffrey Mainda; Mercy Mukuma; et al. (Veterinary World, 2023)
Background and Aim: Inappropriate use of antimicrobials exacerbates antimicrobial resistance (AMR) in the poultry sector. Information on factors driving AMR in the layer poultry sector is scarce in Zambia. This study examined the drivers of AMR in the layer poultry sector in the Lusaka and Copperbelt Provinces of Zambia.